Morphological selection of teak (Tectona grandis) clones resistant to mistletoe infestation - ZAINAL MUTTAQIN; FEBI NURILMALA NUH; ISKANDAR ZULKARNAIN SIREGAR; ARIS WIBOWO; SRI RAHAYU (Society for Indonesian Biodiversity, 2025)
Abstract. Muttaqin Z, Nuh FN, Siregar IZ, Wibowo A, Rahayu S. 2025. Morphological selection of teak (Tectona grandis) clones resistant to mistletoe infestation. Biodiversitas 26: 4851-4864. Until now, study about the teak clones of Jati Plus Perhutani (JPP) resistance to mistletoe, which is very rarely of it in both Indonesia and other regions. The purpose of this study focuses on selecting teak clones with resistance to mistletoe by analyzing their morphological characters. In the study location at East Java, Indonesia, both the Clonal Seed Orchard (CSO) plot in Padangan, the JPP plot and the Seed Production Stand (SPS) plot in KPH Ngawi, the sample plot design follows the modified EFForTS/CRC990 guidelines. By contrast, the JPP plot utilizes the